2021
DOI: 10.1111/epi.16986
|View full text |Cite
|
Sign up to set email alerts
|

Acute thalamic damage as a prognostic biomarker for post‐traumatic epileptogenesis

Abstract: Objective To identify magnetic resonance imaging (MRI) biomarkers for post‐traumatic epilepsy. Methods The EPITARGET (Targets and biomarkers for antiepileptogenesis, epitarget.eu) animal cohort completing T2 relaxation and diffusion tensor MRI follow‐up and 1‐month‐long video‐electroencephalography monitoring included 98 male Sprague‐Dawley rats with traumatic brain injury and 18 controls. T2 imaging was performed on day (D) 2, D7, and D21 and diffusion tensor imaging (DTI) on D7 and D21 using a 7‐Tesla Bruker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
(51 reference statements)
2
10
0
Order By: Relevance
“…Our present findings agree with previous studies showing that hippocampal changes assessed at 6–9 months after TBI differentiate between epileptogenic and nonepileptogenic animals, even though no statistics for differentiation accuracy were provided by earlier reports 10,19,20 . Interestingly, in the EPITARGET cohort analyzed here, we recently showed that thalamic diffusion changes differentiated epileptogenic from nonepileptogenic animals already during the first postinjury weeks 38 . Instead, the severity of cortical damage or its progression were without prognostic value 26 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our present findings agree with previous studies showing that hippocampal changes assessed at 6–9 months after TBI differentiate between epileptogenic and nonepileptogenic animals, even though no statistics for differentiation accuracy were provided by earlier reports 10,19,20 . Interestingly, in the EPITARGET cohort analyzed here, we recently showed that thalamic diffusion changes differentiated epileptogenic from nonepileptogenic animals already during the first postinjury weeks 38 . Instead, the severity of cortical damage or its progression were without prognostic value 26 .…”
Section: Discussionsupporting
confidence: 89%
“…10,19,20 Interestingly, in the EPITARGET cohort analyzed here, we recently showed that thalamic diffusion changes differentiated epileptogenic from nonepileptogenic animals already during the first postinjury weeks. 38 Instead, the severity of cortical damage or its progression were without prognostic value. 26 These data suggest that whole-brain multimodal MRI analysis could prove highly valuable in the study of epileptogenesis and its biomarkers.…”
Section: Hippocampal Parameters Measured At 5 Months Post-tbi Perform...mentioning
confidence: 99%
“…Despite being insulated from the primary site of cortical injury, the ipsilateral thalamus exhibits intensifying secondary neuroinflammation even while the cortical inflammatory response associated with the primary injury abates. This phenomenon has been observed in both rodent models and human patients and has been associated with secondary thalamic neurodegeneration and neuroinflammation after TBI (Holden et al., 2021; Manninen et al., 2021; Ramlackhansingh et al., 2011; Scott et al., 2010), and after stroke (Cao et al., 2020; Kuchcinski et al., 2017; Langen et al., 2007; Pappata et al., 2000; Paz et al., 2010; Paz et al., 2013; Weishaupt et al., 2016).…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, the thalamus has been implicated in a variety of secondary poststroke and TBI impairments in both rodent models and human patients, including cognitive dysfunction, sleep disruption, and sensory‐perceptual errors (Cao et al., 2020; Grossman & Inglese, 2016; Grossman et al., 2012; Kuchcinski et al., 2017; Sandsmark et al., 2017). In particular, while moderate neuroinflammation may serve a neuroprotective function (Fraser et al., 2010), thalamic inflammation after TBI has been associated with sleep‐wake disruptions (Hazra et al., 2014) as well as abnormal sleep spindles and epileptic activity (Manninen et al., 2021; Holden et al., 2021). Moreover, the degree of preservation of thalamic circuitry after cortical ischemia is a predictor of motor performance after TBI in humans (Binkofski et al., 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Like in humans with PTE, progressive brain damage involves epileptogenic regions, including the cerebral cortex and hippocampus [ 7 , 19 , 20 ]. The progression of cortical and hippocampal atrophy and spatial distortion, however, varies significantly between animals over time [ 7 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%